2006
DOI: 10.1002/pssa.200667005
|View full text |Cite
|
Sign up to set email alerts
|

Laser technologies applied to the fabrication and characterization of bulk Bi‐2212 superconducting materials for power applications

Abstract: Lasers are adequate tools in the processing and characterization of materials. The Applied Superconductivity group at the Aragón Materials Science Institute has been applying different laser techniques in the processing, machining and characterization of bulk high temperature superconductors for high power applications. Textured bulk Bi-2212 superconductors have been obtained using laser melting zone techniques. We have produced thin bars, monoliths and coatings on metallic and ceramic substrates. Ablation tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…In early studies [14,16], it was observed that the BSCCO thin films produced by PLD have exhibited poor supercondu cting properties compared to alternative fabricatio n techniques. It has been recently reported, for example, that high T C and J C values may be obtained for these high-T C materials produced by continuous laser irradiation methods [40][41][42]. On the other hand, it was reported that a significant improvement in supercon ducting propertie s of the thin films could be obtained, deposited by PLD and applying a post-anneal ing heat treatment in an atmosph ere containing a mixture of argon and oxygen (Ar: 93, O 2 : 7) [9,13,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…In early studies [14,16], it was observed that the BSCCO thin films produced by PLD have exhibited poor supercondu cting properties compared to alternative fabricatio n techniques. It has been recently reported, for example, that high T C and J C values may be obtained for these high-T C materials produced by continuous laser irradiation methods [40][41][42]. On the other hand, it was reported that a significant improvement in supercon ducting propertie s of the thin films could be obtained, deposited by PLD and applying a post-anneal ing heat treatment in an atmosph ere containing a mixture of argon and oxygen (Ar: 93, O 2 : 7) [9,13,15,17].…”
Section: Introductionmentioning
confidence: 99%
“…After thermal treatment, typical resistance values of these contacts are below 1 lX. 39 Moreover, for the magnetic measurements, smaller pieces ($0.5 cm long) were cut from as-grown bars and directly subjected to the thermal treatment process. After these annealing processes, some of the samples were kept to be used as reference, while others were subjected to secondary annealing treatments.…”
Section: Methodsmentioning
confidence: 99%
“…In the case of the field parallelly applied with respect to the ab-plane, the current mostly flows along the c-axis and encounters a higher number of grain boundaries due to the intrinsic nature of Bi-2212 phase (see Figure 6b). The preferential growth of this phase is along the ab-plane, which allows the production of grains easily exceeding 100 m in the a-, or b-direction using the LFZ technique [30]. On the other hand, they are in the range of tenths of nm in the c-direction producing a drastic raise on the number of grain boundaries which cause a decrease of J c in this direction.…”
Section: Magnetic Relaxation Investigationsmentioning
confidence: 99%